Analysis of the Effect of Implementing Seller’s Integrity and Buyer’s Prudence on Fraudulent Acts in E-Commerce in Indonesia - Asri Noer Rahmi; Ade Wirman Syafei; Silvia Siska Pratiwi; Fiona Daffa Darmawan (Association of Certified Fraud Examiners Indonesia Chapter, 2022)
The aim of this research is to analyze the effect of implementing seller’s integrity and buyer’s prudence on the fraudulent acts in e-commerce in Indonesia. This research needs to be discussed because of the increase of e-commerce usage as a platform to do transactions between sellers and buyers. The used design in this research is quantitative descriptive research with the secondary data type. The sampling technique used is the purposive sampling technique with e-commerce in Indonesia as the population and total of 200 stores as qualified samples. The data analysis method used is the parametric statistic method with multiple linear regression as the hypothesis testing method. This research used SPSS Version 25 software to process the data. The result shows that the seller’s integrity has a negative significance effect on fraudulent act, while the buyer’s prudence has a positive significant effect on fraudulent act.